A new species of Zercoseius (Acari: Mesostigmata: Blattisociidae) from Brazil - Santos, Jandir C.; Borges, Vinicius; Castilho, Raphael C. (Zootaxa, 2023)
Zercoseius luizdequeirozi n. sp. is described based on adult females collected from soil/litter samples taken from disturbed areas of the natural vegetation of the Brazilian Atlantic Forest biome. This new species differs from Zercoseius spathuliger (Leonardi, 1899), presently the only species included in this genus, reported so far from Europe, northern Africa and northwestern USA, more obviously by the shape of the dorsal shield setae and by having seta s1.